Pseudomonas californiensis sp. nov. and Pseudomonas quasicaspiana sp. nov., isolated from ornamental crops in California. Issue 11 (2nd November 2022) - Carvalho, Renato; Albu, Sebastian; Timilsina, Sujan; Minsavage, Gerald V.; Paret, Mathews L.; Jones, Jeffrey B.
Abstract : Five bacterial strains were isolated from symptomatic leaves of Achillea millefolium, Delphinium sp. and Hydrangea sp. in California. Colonies isolated on King's medium B (KMB) appeared white, mucoid and round, similar to Pseudomonas species. Phylogenetic analyses based on 16S rRNA, rpoB, rpoD and gyrB genes placed the bacteria into three distinct groups within Pseudomonas that were most closely related to Pseudomonas viridiflava, Pseudomonas cichorii or Pseudomonas caspiana . To further characterize the strains, phenotypic analyses and the following tests were performed: fatty acid methyl ester composition, LOPAT, fluorescence on KMB, Biolog assay, and transmission electron microscopy. Finally, whole genome sequencing of the strains was conducted, and the sequences were compared with reference genomes of Pseudomonas species based on average nucleotide identity (ANI). The first group, which consists of three strains isolated from delphinium, hydrangea and achillea, had 95.6–96.9 % pairwise ANI between each other; the second group consists of two strains isolated from delphinium that had 100 % pairwise ANI. Although comparisons of the two groups with publicly available genomes revealed closest relationships with P. viridiflava (91.6 %), P. caspiana (88.3 %) and P. asturiensis (86.7 %), ANI values were less than 95 % compared to all validly published pseudomonads. Combining genomic and phenotypic data, we conclude that these strains represent two new species and the names proposed are Pseudomonas quasicaspiana sp. nov. (type strain DSMZ 11 30 42 T =LMG 32 434 T ) for the strains isolated from delphinium, achillea and hydrangea and Pseudomonas californiensis sp. nov. (DSMZ 11 30 43 T =LMG 32 432 T ) for the two strains isolated from delphinium. The specific epithets quasicaspiana and californiensis were selected based on the close phylogenetic relationship of strains with P. caspiana and on the geographic location of isolation, respectively.